Whole-body MRI as an unconventional diagnostic tool in a pediatric patient with systemic infection. Issue 11 (4th December 2014) - Picco, Paolo; Naselli, Aldo; Pala, Giovanna; Rizzo, Francesca; Damasio, Beatrice; Buoncompagni, Antonella; Martini, Alberto
Anaplasma phagocytophilum, an obligate intracellular bacterium, is the causative agent of human granulocytic anaplasmosis (HGA), a tickborne infection usually manifesting as fever, malaise, cytopenia, spleen enlargement, and hepatitis. Herein, we report a case of a 14-year-old girl with HGA whose whole-body magnetic resonance imaging (MRI) disclosed an unusual picture characterized by small, widespread punctuate millimetric nodules, hypointense on T1-weighted and hyperintense on STIR sequences. This firstly reported finding may represent an alternative tool for identifying atypical infectious diseases.